The first aquatic insect fossil from the Cenomanian Konservat-Lagerstätte of Haqel (Lebanon) fills a gap in the fossil record of giant water bugs (Heteroptera: Belostomatidae) - Boderau, Mathieu; Nel, André; Maksoud, Sibelle; Abi-Saad, Pierre; Azar, Dany (Zootaxa, 2024)
Libanobelostoma calineae gen. et sp. nov., the first mid-Cretaceous giant water bug, is characterized, illustrated and described from the fossil fish Konservat-Lagerstätte of Haqel, Lebanon. This new discovery is important for both the fossil record of the Belostomatidae and for increasing our understanding of the paleoenvironment of Haqel. The new genus displays a combination of synapomorphies and symplesiomorphies for Belostomatidae, along with putative autapomorphies justifying its taxonomic treatment. Together with Libanoaeshna mikhaeli Azar et al., 2024 they represent the first insect discoveries in the fossil fish Konservat-Lagerstätte of Haqel, making it an additional palaeoentomological site to the numerous other sites in Lebanon.